The Effect of Motivational Interview on Puberty Knowledge and Practice among Adolescent Girls - Sarah Mohamadi; Omid Garkaz; Seyed Abbas Mousavi; Afsaneh Keramat; Shahrbanoo Goli; Zahra Motaghi (Kashan University of Medical Sciences, 2021)
Background: Adolescence is a critical stage of life with a significant role in reproduction and fertility. Interventions are needed to promote the health of adolescent girls as prospective mothers. Objectives: This study aimed to investigate the effects of motivational interviewing on adolescent girls' puberty knowledge and practice. Methods: This quasi-experimental study was conducted in 2018 on 240 eighth-grade female students recruited through multistage sampling from ten high schools in Shahroud, Iran. Schools were allocated into an intervention group and a control group through simple randomization. Participants in the intervention group received a five-session puberty-related motivational interviewing intervention. Puberty knowledge and practice in both groups were assessed before, immediately after, and 1 month after the intervention. Data were analyzed through the Chi-square and the independent-samples t-tests and the repeated-measures analysis of variance. Results: Participants' age was 14.47 ± 0.51 years, on average. About 70% of them had poor or moderate puberty knowledge. Although there was no statistically significant between-group difference respecting the mean scores of puberty knowledge and practice at pretest (P > 0.05), the mean scores of puberty knowledge and practice in the intervention group were significantly higher than the control group at both posttests (P = 0.001). Conclusion: Motivational interviewing is effective in improving adolescent girls' puberty knowledge and practice.